Functions of beta2‐adrenergic receptor in human periodontal ligament cells. Issue 12 (1st March 2020) - Hamano, Sayuri; Tomokiyo, Atsushi; Hasegawa, Daigaku; Yuda, Asuka; Sugii, Hideki; Yoshida, Shinichiro; Mitarai, Hiromi; Wada, Naohisa; Maeda, Hidefumi
Abstract: Adrenergic receptors (ARs) are receptors of noradrenalin and adrenalin, of which there are nine different subtypes. In particular, β2 adrenergic receptor (β2‐AR) is known to be related to the restoration and maintenance of homeostasis in bone and cardiac tissues; however, the functional role of signaling through β2‐AR in periodontal ligament (PDL) tissue has not been fully examined. In this report, we investigated that β2‐AR expression in PDL tissues and their features in PDL cells. β2‐AR expressed in rat PDL tissues and human PDL cells (HPDLCs) derived from two different patients (HPDLCs‐2G and ‐3S). Rat PDL tissue with occlusal loading showed high β2‐AR expression, while its expression was downregulated in that without loading. In HPDLCs, β2‐AR expression was increased exposed to stretch loading. The gene expression of PDL‐related molecules was investigated in PDL clone cells (2‐23 cells) overexpressing β2‐AR. Their gene expression and intracellular cyclic adenosine monophosphate (cAMP) levels were also investigated in HPDLCs treated with a specific β2‐AR agonist, fenoterol (FEN). Overexpression of β2‐AR significantly promoted the gene expression of PDL‐related molecules in 2 to 23 cells. FEN led to an upregulation in the expression of PDL‐related molecules and increased intracellular cAMP levels in HPDLCs. In both HPDLCs, inhibition of cAMP signaling by using protein kinase A inhibitor suppressed the FEN‐induced gene expression of α‐smooth muscle actin. Our findings suggest that the occlusal force is important for β2‐AR expression in PDL tissue and β2‐AR is involved in fibroblastic differentiation and collagen synthesis of PDL cells. The signaling through β2‐AR might be important for restoration and homeostasis of PDL tissue. Abstract : The expression of β2 adrenergic receptor (β2‐AR) was increased in human periodontal lgament cells (HPDLCs) exposed to stretch loading, and its protein expression was decreased in rat periodontal ligament (PDL) tissue subjected to reduced occlusal loading. Fenoterol, a specific β2‐AR agonist, led to an upregulation in the expression of PDL‐related molecules and increased intracellular cyclic adenosine monophosphate levels in HPDLCs. Therefore, it was suggested that β2‐AR in PDL tissues might be involved in PDL homeostasis.